Study of regional dilution and transformation processes of the air pollution from road transport. (8th February 2011) - Ganev, Kostadin; Syrakov, Dimiter; Todorova, Angelina; Gadzhev, Georgi; Miloshev, Nikolay; Prodanova, Maria
The objective of this work is to study in detail the dilution processes of the plumes and the chemical transformations of pollutants generated by road transport. The numerical simulations are carried out using the MODELS-3 nesting abilities, downscaling to a horizontal resolution of 10 km, the innermost domain including a region with very intensive road transport – the city of London and its 'footprint'. A large number of numerical experiments were carried out, which makes it possible to distinguish the relative contribution of different air pollution factors for different spatial resolutions of the emission inventories and meteorological fields.